2016
DOI: 10.2169/internalmedicine.55.6080
|View full text |Cite
|
Sign up to set email alerts
|

Adult-onset Invasive <i>Haemophilus influenzae</i> Type f Caused by Acute Lower Leg Cellulitis

Abstract: In Japan, routine Haemophilus influenzae type b (Hib) vaccination began in 2013. Thus, similar to other countries, a strain shift is expected in the near future. We experienced a case of H. influenzae type f (Hif) bacteremia in a 66-year-old man. The primary focus of the infection was the soft tissue of the left lower leg, which is an extremely rare origin in adults. Subsequently, we conducted multilocus sequence typing and identified the strain as sequence type 124, which is the most common invasive strain of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…The ages in the eight adult cases ranged from 42 to 86 years. Four patients had a form of immunosuppression (steroid use, chronic lymphocytic leukemia, immunoglobulin G (IgG) 4 deficiency, and HIV with a CD4 count of 530/ul (as in our case) [1,5,8]. One case involved solely the upper extremities and a second involved the hand and foot [2,6].…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…The ages in the eight adult cases ranged from 42 to 86 years. Four patients had a form of immunosuppression (steroid use, chronic lymphocytic leukemia, immunoglobulin G (IgG) 4 deficiency, and HIV with a CD4 count of 530/ul (as in our case) [1,5,8]. One case involved solely the upper extremities and a second involved the hand and foot [2,6].…”
Section: Discussionmentioning
confidence: 74%
“…Cellulitis of the extremities secondary to HI is even more uncommon. A review of the literature yielded eight cases of cellulitis of the extremities in adults and another four cases in children [1][2][3][4][5][6][7][8][9][10][11]. All these patients presented with HI bacteremia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports indicated that comorbid diseases, such as chronic obstructive pulmonary disease, malignancy, and immunosuppression, are risk factors for invasive infections caused by H. influenzae (3). To compare this case with the trend in recent invasive Hif infections, the authors surveyed case reports on PubMed using the search terms "H. influenzae type f" and "adult" and used the results to build a summary table (Table 4) of case report of invasive Hif infections since 2013, when routine immunization against Hib started in Japan (18)(19)(20)(21)(22)(23)(24). In these cases, the median age was 63 years old, with some differences in sex.…”
Section: Discussionmentioning
confidence: 99%
“…Five cases of invasive disease due to Hif were recently reported in Japan (6-8), all occurred in immunocompetent young children and adults with underlying conditions. Four of the five cases were considered “typical” (i.e., patients were infected with ampicillin-susceptible Hif).…”
Section: Introductionmentioning
confidence: 99%